Expression data analysis to identify key target genes in visceral fat tissue associated with obstructive sleep apnea - Chen, J H; Yang, R; Wang, Y P; Zhang, W (European review for medical and pharmacological sciences, 2015)
The purpose of this study was to screen key genes related to mechanisms and consequences of obstructive sleep apnea (OSA)-induced perturbations in visceral fat tissue depots. Microarray data of GSE38792, comprising 10 visceral fat samples from OSA patients and 8 visceral fat samples from control subjects, was obtained from the Gene Expression Omnibus (GEO) database. Differentially expressed genes (DEGs) were identified in visceral fat samples from OSA patients compared with controls using Bioconductor package limma. Gene Ontology (GO) and pathway enrichment analyses were carried out to identify significantly altered biological functions. Furthermore, a protein-protein interaction (PPI) network was constructed with STRING database and visualized with Cytoscape software. Additionally, the transcriptional regulatory relationships were screened using UCSC ENCODE Genome Browser. A total of 380 DEGs were identified, of which 188 were up-regulated and 192 were down-regulated. The DEGs were involved in different GO terms and pathways, mainly associated with metabolism such as proteolysis. PPI network analysis revealed that Actin, Alpha 1, Skeletal Muscle (ACTA1), Histone Deacetylase 2 (HDAC2), and Small Ubiquitin-Like Modifier 1 (SUMO1) were hub proteins. In addition, HDAC2 was shown to encode a transcription factor (TF) and it could regulate 3 DEGs. Genes such as ACTA1, HDAC2, and SUMO1 were presumed to play critical roles in the mechanisms and consequences of OSA-induced perturbations in visceral fat tissue depots, which may be useful for deeply studying the mechanisms underlying OSA.